An autogenic acid system, preparation method and application thereof
Patent Information
- Application Number
- CN202611050292.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]本公开提供了一种自生酸体系及制备方法和应用,以至少解决现有技术中存在的自生酸体系生酸反应速率与施工需求难以匹配、无法在高温储层中实现深部集中生酸的技术问题
本公开以核壳结构的温敏型纳米催化剂为核心,通过其独特的温度响应催化特性,解决了高温储层中自生酸体系生酸位置不可控的问题,实现了地面配制稳定、井筒运输安全、储层深部集中反应的精准深度酸化目标。在井筒低温区,催化剂维持低活性,体系保持低腐蚀性,有效降低了高温高压环境下对井下管柱和工具的腐蚀风险;在储层高温区,催化活性被激发,有机酸在目标位置集中生成并直接参与酸岩反应,避免了活性酸在近井地带的无效消耗,有效作用距离比常规酸化和普通自生酸提高50%以上,能沟通远端的天然裂缝和溶洞,大幅提高储层改造体积与增产效果。同时,通过改变纳米催化剂的活性组分种类、负载量及颗粒尺寸,能够精细调控体系的温度响应范围与生酸动力学参数,以适应不同温度和物性的储层条件。催化剂的可磁性回收则进一步降低了成本和环境污染。因此,本公开的自生酸体系兼具精准催化、深度作用、安全可控、经济环保等优势,为高温深部碳酸盐岩储层的高效酸化改造提供了全新的技术途径。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of oilfield chemical technology, and in particular to an autogenous acid system, its preparation method, and its application. Background Technology
[0002] In the field of oil and gas well production enhancement, carbonate reservoirs are often put into production and enhanced using acidizing or acid fracturing techniques. For high-temperature deep carbonate reservoirs, conventional inorganic acids (such as hydrochloric acid) have prominent problems such as excessively fast reaction rates, short effective range, severe corrosion of downhole tubing, and the tendency to cause excessive etching in the near-wellbore zone, leading to uneven fluid inflow. To address these issues, existing technologies have developed organic acid systems (such as acetic acid and formic acid) and chemically slow-release acid systems (such as gelling acids, emulsified acids, and authigenic acids).
[0003] However, existing autogenous acid systems face a core contradiction in high-temperature reservoir applications: the acid generation reaction rate is difficult to match with construction requirements, there is a lack of autogenous acid systems that can actively regulate the kinetics of acid generation reaction in different temperature ranges, and they cannot simultaneously meet the requirements of wellbore transportation safety and efficient etching of reservoir depth. Summary of the Invention
[0004] This disclosure provides an autogenous acid system, its preparation method, and its application, thereby at least solving the technical problems in the prior art where the acid generation reaction rate of the autogenous acid system is difficult to match with construction requirements and cannot achieve deep concentrated acid generation in high-temperature reservoirs.
[0005] According to a first aspect of this disclosure, an autogenous acid system is provided, comprising: an autogenous acid precursor, the autogenous acid precursor comprising at least one ester compound capable of generating an organic acid in a hydrolysis reaction; and a nanocatalyst having a magnetic core, a mesoporous shell coating the magnetic core, and a catalytically active component supported within the pores of the mesoporous shell; wherein the nanocatalyst exhibits first catalytic activity for the hydrolysis reaction of the autogenous acid precursor at temperatures below a first temperature threshold; and second catalytic activity for the hydrolysis reaction of the autogenous acid precursor at temperatures above a second temperature threshold, wherein the first temperature threshold is lower than the second temperature threshold and the second catalytic activity is higher than the first catalytic activity.
[0006] Specifically, this disclosure utilizes a three-layered nanocatalyst with a magnetic core, a mesoporous shell, and catalytically active components within the pores as its core. Leveraging the catalyst's unique temperature-responsive catalytic properties, it achieves intelligent control over the hydrolysis reaction of authigenic acid precursors. In the low-temperature zone of the wellbore (below the first temperature threshold, typically <100°C), the catalyst maintains low primary catalytic activity, resulting in slow hydrolysis of ester precursors. The system safely passes through the wellbore in a low-corrosiveness, high-stability state. When the system enters the high-temperature reservoir depths with the injection fluid (above the second temperature threshold, typically >120°C), the catalyst is thermally activated, exhibiting significantly enhanced secondary catalytic activity. This leads to an order-of-magnitude increase in the ester hydrolysis rate, resulting in the rapid and concentrated generation of high-concentration organic acids at depth. This, in turn, efficiently etches the reservoir rock, achieving true deep acidification. This system breaks through the traditional model where acidifying fluids maintain high reactivity throughout the wellbore and reservoir, constructing an acidification technology pathway that features stable surface preparation, safe wellbore transportation, and deep reservoir reaction. The synergistic effect of the components avoids the severe corrosion risk of high-concentration acid to the tubing under high-temperature conditions, while solving the problems of premature acid generation in the near-wellbore zone of high-temperature reservoirs and insufficient acid concentration in deep reservoirs, which limits the effective operating distance of existing self-generating acid systems.
[0007] In one embodiment, the catalytically active component includes a transition metal oxide; the transition metal oxide is at least one of copper oxide (CuO), zinc oxide (ZnO), and manganese dioxide (MnO2), preferably copper oxide (CuO).
[0008] Specifically, using the aforementioned transition metal oxides as catalytically active components can effectively reduce the activation energy of the ester hydrolysis reaction, enabling it to exhibit a nonlinear catalytic enhancement effect within a specific temperature window. By changing the type of transition metal oxide, the active temperature window and catalytic intensity of the catalyst can be controlled, allowing the authigenic acid system to adapt to a wider formation temperature range of 90℃ to 150℃ or even longer. Copper oxide exhibits high catalytic activity above 120℃, while zinc oxide and manganese dioxide can provide differentiated catalytic response characteristics in different temperature ranges, offering multiple options to meet the actual operating conditions of different geothermal gradients and reservoir depths.
[0009] In one embodiment, the magnetic core is nano-iron oxide particles, the mesoporous shell is a mesoporous silica shell, and the catalytically active component is copper oxide ultrafine nanoparticles loaded in the pores of the mesoporous silica shell.
[0010] Specifically, using nano-ferric oxide as the magnetic core endows the catalyst with recyclability under the influence of an external magnetic field, providing a physical basis for the separation, recovery, and reuse of the catalyst after acidification. A shell of silica with a regular mesoporous structure provides a support for the uniform loading of copper oxide ultrafine nanoparticles due to its high specific surface area and ordered channels. Simultaneously, the mesoporous channels allow reactant molecules (esters and water) to freely enter and exit the catalytic active center, while the physical barrier effect of the shell effectively protects the magnetic core from acidic environment corrosion and inhibits the aggregation and deactivation of active components under high temperature and high pressure conditions. This core-shell structure endows the catalyst with high catalytic activity, excellent structural stability, and convenient magnetic recovery performance.
[0011] In one embodiment, the concentration of the nanocatalyst in the authigenic acid system is 0.1% w / v to 1.0% w / v, and the weight of the authigenic acid precursor is 15 to 30 parts.
[0012] Specifically, by controlling the concentration of the nanocatalyst within the range of 0.1% w / v to 1.0% w / v, sufficient catalytic activity can be ensured while avoiding increased costs and potential formation pore blockage risks caused by excessive catalyst use. This concentration range balances catalytic efficiency and engineering economics.
[0013] In one embodiment, the authigenic acid precursor is one or more of methyl formate, methyl acetate, and methyl lactate.
[0014] Specifically, the aforementioned ester compounds are used as precursors for authigenic acids, which, upon hydrolysis, yield formic acid, acetic acid, lactic acid, or mixtures thereof. By selecting a single ester or adjusting the mixing ratio of different esters, the types and concentrations of the final organic acids can be flexibly controlled to adapt to carbonate reservoirs with different mineral compositions and physical properties. For example, in gypsum-bearing reservoirs, the proportion of methyl acetate can be increased to increase acetic acid production, utilizing the chelating effect of acetic acid to reduce the risk of calcium scale deposition.
[0015] In one embodiment, the self-generating acid system further comprises a dispersant and a base liquid; the dispersant is sodium citrate or sodium dodecyl sulfate; and the base liquid is an aqueous solution of potassium chloride or an aqueous solution of ammonium chloride.
[0016] Specifically, by introducing a dispersant, the dispersion uniformity and suspension stability of the nanocatalyst in the base liquid can be effectively improved, preventing the catalyst particles from settling and agglomerating during pumping, and ensuring that the system maintains a uniform and stable suspension state before entering the reservoir. The base liquid is an aqueous solution of potassium chloride or ammonium chloride, which can effectively inhibit the hydration swelling of clay minerals in the reservoir and protect the reservoir permeability.
[0017] According to a second aspect of this disclosure, a method for preparing the above-mentioned authigenic acid system is provided, comprising: mixing an authigenic acid precursor, a nanocatalyst, and a base liquid, adding a dispersant, and stirring until the nanocatalyst is uniformly dispersed in the system to obtain the authigenic acid system; wherein the authigenic acid precursor contains at least one ester compound capable of generating an organic acid in a hydrolysis reaction, and the nanocatalyst has a magnetic core, a mesoporous shell coating the magnetic core, and a catalytically active component supported in the pores of the mesoporous shell; the nanocatalyst exhibits a first catalytic activity for the hydrolysis reaction of the authigenic acid precursor below a first temperature threshold; and a second catalytic activity for the hydrolysis reaction of the authigenic acid precursor above a second temperature threshold, wherein the first temperature threshold is lower than the second temperature threshold and the second catalytic activity is higher than the first catalytic activity.
[0018] The preparation method is simple and can be completed by conventional stirring under normal temperature and pressure conditions. No special equipment is required, and it has good on-site operability and large-scale production feasibility.
[0019] In one embodiment, the nanocatalyst is prepared in advance by: synthesizing magnetic nanoparticles as the magnetic core using a hydrothermal method; coating the magnetic nanoparticles with a mesoporous silica shell using a modified Stöber method; and loading a catalytically active component, including a transition metal oxide, into the pores of the mesoporous silica shell by an impregnation-calcination method.
[0020] Specifically, magnetic nanoparticles are synthesized using a hydrothermal method. Using iron salts as precursors, uniform and highly crystalline nano-iron oxide particles are prepared through a high-temperature solvothermal reaction in a polyol system. The improved Stöber method involves introducing a cationic surfactant as a mesoporous template agent during the hydrolysis and condensation of tetraethyl orthosilicate. After forming a silica coating layer on the surface of the magnetic nanoparticles, the template agent is removed by solvent extraction or calcination to obtain a silica shell with regular and ordered mesoporous channels. The impregnation-calcination method disperses the particles coated with the mesoporous silica shell in a precursor solution containing transition metal salts. Impregnation allows metal ions to enter the mesoporous channels. Subsequently, drying and calcination treatment cause the metal salts to decompose in situ into ultrafine transition metal oxide nanoparticles within the channels, achieving uniform and stable loading of the catalytically active components within the mesoporous channels.
[0021] The pre-preparation method has controllable and reproducible conditions in each step, and can precisely control the particle size and magnetic responsiveness of the magnetic core, the thickness and pore size distribution of the mesoporous shell, and the loading and dispersion state of the catalytically active components, thereby achieving systematic optimization of the temperature response characteristics and catalytic activity of the nanocatalyst.
[0022] According to a third aspect of this disclosure, an application of the aforementioned authigenic acid system is provided, comprising: pumping the authigenic acid system into a wellbore, maintaining the authigenic acid system at a first catalytic activity in an environment below a first temperature threshold within the wellbore, wherein the hydrolysis reaction of the authigenic acid precursor proceeds at a first rate; continuing to inject the authigenic acid system into a reservoir at a temperature above a second temperature threshold, wherein the nanocatalyst is activated to a second catalytic activity, catalyzing the hydrolysis of the authigenic acid precursor at a second rate to generate an organic acid, wherein the second rate is higher than the first rate; and contacting the generated organic acid with the reservoir rock to undergo an acid-rock reaction, thereby etching the reservoir.
[0023] Specifically, during the pumping stage, the self-generated acid system flows downwards along the wellbore. At this time, the wellbore temperature is usually below the first temperature threshold (e.g., 100°C), and the nanocatalyst maintains a low first catalytic activity. The hydrolysis reaction of ester precursors proceeds at a slow first rate. The system maintains a safe state of low acid concentration and low corrosivity throughout the long wellbore transport process, fundamentally eliminating the severe corrosion risk to the tubing and downhole tools caused by high-temperature concentrated acid in traditional acidizing operations. It can also simplify or even eliminate the use of high-concentration corrosion inhibitors, reducing construction costs and safety risks. As the system continues to be injected and penetrates deeper into the formation, the ambient temperature gradually increases. When the temperature crosses the second temperature threshold (e.g., above 120°C), the nanocatalyst is thermally activated, and its catalytic activity jumps to a significantly enhanced second catalytic activity. The hydrolysis rate of ester precursors increases by orders of magnitude, and high-concentration fresh organic acids are generated rapidly and concentrated in the deep reservoir at a second rate much higher than the first rate. The organic acids generated at this time, in their highest concentration and most active state, directly contact the reservoir rock, undergoing an acid-rock reaction and efficiently etching the reservoir pore throats and fracture walls.
[0024] In one embodiment, the application further includes: recovering and reusing the nanocatalyst carried in the backflow solution after acidification.
[0025] Specifically, by utilizing the response characteristics of the Fe3O4 magnetic core in the nanocatalyst to an applied magnetic field, the catalyst can be efficiently recovered from the flowback fluid using a wellhead magnetic separation device or a downhole magnetic adsorption tool. After simple acid washing, water washing, and drying, the recovered catalyst retains over 97% of its catalytic activity and can be directly recycled for the preparation of the next batch of authigenic acid systems. This recycling process not only significantly reduces the cost of using nanocatalysts and improves process economics, but also reduces the residue of metal ions in the formation, resulting in significant environmental benefits.
[0026] Through the above technical solutions, the self-generating acid system, preparation method, and application disclosed herein have at least the following beneficial effects: This disclosure utilizes a core-shell structured, temperature-sensitive nanocatalyst as its core. Through its unique temperature-responsive catalytic properties, it solves the problem of uncontrollable acid generation location in high-temperature reservoirs, achieving precise deep acidification with stable surface preparation, safe wellbore transportation, and concentrated deep-reservoir reactions. In the low-temperature zone of the wellbore, the catalyst maintains low activity, and the system retains low corrosivity, effectively reducing the corrosion risk to downhole tubing and tools under high-temperature and high-pressure conditions. In the high-temperature zone of the reservoir, catalytic activity is activated, and organic acids are concentrated at the target location and directly participate in the acid-rock reaction, avoiding the ineffective consumption of active acids in the near-wellbore zone. The effective action distance is increased by more than 50% compared to conventional acidification and ordinary authigenic acidification, enabling communication with distant natural fractures and caverns, significantly increasing reservoir stimulation volume and production enhancement. Simultaneously, by changing the types, loading, and particle size of the active components of the nanocatalyst, the temperature response range and acid generation kinetic parameters of the system can be finely controlled to adapt to reservoir conditions with different temperatures and properties. The magnetic recovery of the catalyst further reduces costs and environmental pollution. Therefore, the self-generating acid system disclosed in this paper has the advantages of precise catalysis, deep action, safety and controllability, and economic and environmental protection, providing a brand-new technical approach for the efficient acidification transformation of high-temperature deep carbonate reservoirs.
[0027] It should be understood that the description in this section is not intended to identify key or essential features of the embodiments of this disclosure, nor is it intended to limit the scope of this disclosure. Other features of this disclosure will become readily apparent from the following description. Detailed Implementation
[0028] To make the objectives, features, and advantages of this disclosure more apparent and understandable, the technical solutions in the embodiments of this disclosure will be clearly and completely described below in conjunction with the embodiments of this disclosure. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments of this disclosure, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this disclosure.
[0029] This preparation example demonstrates the preparation of the core-shell structured nanocatalyst (Fe3O4@mSiO2-CuO) used in this disclosure. The specific steps are as follows: First, Fe3O4 magnetic nanoparticles were synthesized using a hydrothermal method. Then, a mesoporous silica (mSiO2) shell was coated onto the surface of the obtained Fe3O4 particles using a modified Stöber method. Finally, copper oxide (CuO) nanoparticles were loaded into the pores of the mesoporous silica shell using an impregnation-calcination method to obtain the nanocatalyst.
[0030] Example 1: This embodiment prepared an acid-generating system enhanced with a nanocatalyst.
[0031] By weight, 20 parts of methyl formate were used as the authigenic acid precursor, 0.6 parts of the nanocatalyst (Fe3O4@mSiO2-CuO) prepared in the above preparation example were used, 0.3 parts of sodium citrate were used as the dispersant, and the balance was a 3% potassium chloride aqueous solution. The sum of the weight parts of the above components was 100. The components were mixed at room temperature and stirred thoroughly to obtain a homogeneous and stable nanocatalyst-enhanced thermochemical authigenic acid system.
[0032] Example 2: This embodiment prepared an acid-generating system enhanced with a nanocatalyst.
[0033] By weight, 20 parts of methyl acetate were used as the authigenic acid precursor, 0.6 parts of the nanocatalyst (Fe3O4@mSiO2-CuO) prepared in the above preparation example were used, 0.3 parts of sodium citrate were used as the dispersant, and the balance was a 3% potassium chloride aqueous solution. The sum of the weight parts of the above components was 100. The components were mixed at room temperature and stirred thoroughly to obtain a homogeneous and stable nanocatalyst-enhanced thermochemical authigenic acid system.
[0034] Example 3: This embodiment prepared an acid-generating system enhanced with a nanocatalyst.
[0035] By weight, 20 parts of a mixture of methyl formate and methyl acetate in a 1:1 mass ratio were used as the authigenic acid precursor, 0.6 parts of the nanocatalyst (Fe3O4@mSiO2-CuO) prepared in the above preparation example were used as the dispersant, and the balance was a 3% potassium chloride aqueous solution. The sum of the weight parts of the above components was 100. The components were mixed at room temperature and stirred thoroughly to obtain a homogeneous and stable nanocatalyst-enhanced thermochemical authigenic acid system.
[0036] Comparative Example 1: This comparative example prepared an autogenous acid system without nanocatalysts.
[0037] Take 20 parts by weight of methyl acetate, 0.3 parts by weight of sodium citrate, and the remainder is a 3% potassium chloride aqueous solution. The sum of the weight parts of the above components is 100. Mix the components thoroughly to obtain the control system.
[0038] Comparative Example 2: This comparative example uses a standard hydrochloric acid solution as a control.
[0039] A 20% hydrochloric acid solution can be used directly instead of the nanocatalyst-enhanced thermochemical acid system of this disclosure.
[0040] Experimental example: The following performance tests were performed on the systems prepared in Examples 1-3 and Comparative Examples 1-2.
[0041] Core permeability testing: Carbonate cores with a diameter of 2.5 cm and a length of 10 cm were selected. First, the core was saturated with simulated formation water to determine the initial permeability (K1). Then, a suspension containing fine kaolinite particles was injected to establish a damaged zone, and the permeability after damage was determined (K2). Under simulated formation temperature (120℃) and confining pressure, 0.5 times the pore volume (PV) of the test fluid was injected into the core at a constant flow rate (0.5 mL / min) to simulate a shut-in reaction for 4 hours. Afterward, reverse displacement was performed, the flowback fluid was collected, and the permeability of the core after acid treatment was determined (K3).
[0042] Static dissolution experiment: Weigh a 20g calcium carbonate rock slice and completely immerse it in the acid solution to be tested. React at the set temperature (120℃) for 2 hours. After the reaction, remove the rock slice, wash it with deionized water, dry it, and weigh it again. Calculate the dissolution rate (percentage of weight loss) and the dissolution rate (weight loss per unit time, g / h) based on the difference in mass of the rock slice before and after the reaction.
[0043] Corrosion test: In accordance with the petroleum and natural gas industry standard SY / T 5405, N80 steel sheets were immersed in the working solution to be tested and the control acid solution, respectively, and tested for 24 hours at 25℃ and 120℃. After the test, the steel sheets were removed, the corrosion weight loss was measured, and the average corrosion rate (mm / a) was calculated.
[0044] Catalyst recovery and reuse experiment: The working solution after the reaction was magnetically separated using a magnet to recover the nano-catalyst. The recovered catalyst was then subjected to simple acid washing, water washing, and drying treatment before being reused in acid generation kinetic tests to evaluate the retention rate (%) of its catalytic activity.
[0045] The results of the above tests are summarized in Table 1.
[0046] Table 1 Performance evaluation results of each scheme
[0047] Combining Example 1 and Comparative Example 1, and referring to Table 1, it can be seen that Example 1, using a self-generating acid system enhanced with a nanocatalyst (Fe3O4@mSiO2-CuO), achieved a dissolution rate of 92% and a dissolution rate of 9.2 g / h for calcium carbonate rock fragments under simulated reservoir conditions at 120℃. After acidification, the core permeability recovered from 75 mD after damage to 198 mD. In contrast, under identical conditions, Comparative Example 1, without the addition of a nanocatalyst, relied solely on its own hydrolysis to generate acid, resulting in a significant decrease in the dissolution rate to 34% and a dissolution rate of only 3.4 g / h. After acidification, the permeability only recovered to 124 mD. The comparison shows that the introduction of the nanocatalyst significantly reduced the activation energy of the ester hydrolysis reaction, leading to an order-of-magnitude increase in the acid generation rate and dissolution efficiency. Furthermore, Example 1 achieved a catalyst recovery retention rate of 98%, demonstrating the excellent reusability of this core-shell magnetic catalyst. The above results fully demonstrate the core catalytic enhancement effect of the core-shell structured nanocatalyst in this disclosure on the acid generation reaction of the self-generating acid system, as well as the recyclability advantage conferred by the magnetic core.
[0048] Based on the combined results of Example 1 and Comparative Example 2, and referring to Table 1, it can be seen that the corrosion rate (92%) and corrosion speed (9.2 g / h) of Example 1 at 120°C are basically equivalent to those of Comparative Example 2 with 20% conventional hydrochloric acid (92% corrosion rate, 9.2 g / h), and the permeability recovery levels after acidification are similar. However, at a wellbore temperature of 25°C, the corrosion speed of the N80 steel sheet in Example 1 is only 0.056 mm / a, while the corrosion speed of the conventional hydrochloric acid in Comparative Example 2 is as high as 1.021 mm / a, a difference of nearly 20 times; at a reservoir temperature of 120°C, the corrosion speed of Example 1 (3.124 mm / a) is also significantly lower than that of Comparative Example 2 (4.355 mm / a). This indicates that the self-generating acid system of this disclosure produces almost no free acid during the low-temperature transport stage in the wellbore, posing an extremely low risk of corrosion to downhole tubing and tools. Only after entering the high-temperature reservoir is the system catalytically activated to rapidly generate acid, achieving a temperature-responsive catalytic acid generation mechanism that provides both low-temperature corrosion inhibition and high-temperature high efficiency. These results fully demonstrate the technical advantages of this disclosure, which uses nanocatalysts to regulate acid generation kinetics, significantly reducing the risk of tubing corrosion while ensuring efficient reservoir etching.
[0049] Based on Examples 1, 2, and 3 and referring to Table 1, it can be seen that, under the same test conditions, Examples 1 (with methyl formate as the precursor), 2 (with methyl acetate as the precursor), and 3 (with a 1:1 mixture of methyl formate and methyl acetate as the precursor) exhibited dissolution rates of 92%, 91%, and 93%, respectively, and dissolution rates of 9.2 g / h, 9.1 g / h, and 9.3 g / h, respectively. After acidification, the core permeability recovered to 198 mD, 183 mD, and 194 mD, respectively. All performance indicators were highly similar and significantly superior to Comparative Example 1. This indicates that the self-generating acid system of this disclosure has good compatibility with different ester precursors. Regardless of whether methyl formate, methyl acetate, or a mixture thereof is used, efficient and controllable acid generation can be achieved under the catalysis of nanocatalysts. These results fully demonstrate that the technical solution of this disclosure has broad applicability to raw materials and process robustness, allowing for flexible selection of the type of self-generating acid precursor based on on-site costs and supply conditions.
[0050] Combining the catalyst recovery retention rates (98%, 97%, and 97%) in Examples 1, 2, and 3, it can be seen that the magnetic core-shell structured nanocatalyst of this disclosure retains over 97% of its catalytic activity after a complete acidification process and magnetic separation and recovery. This means that the catalyst can be effectively recovered and reused multiple times, significantly reducing construction costs and minimizing nanomaterial residues and potential metal ion pollution in the formation. These results fully demonstrate the outstanding advantages of this disclosed technical solution in terms of environmental friendliness and economy, achieving the dual goals of high-efficiency catalysis and green sustainability.
[0051] It should be understood that the various forms of processes shown above can be used to rearrange, add, or delete steps. For example, the steps described in this disclosure can be executed in parallel, sequentially, or in different orders, as long as the desired result of the technical solution disclosed in this disclosure can be achieved, and this is not limited herein.
[0052] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this disclosure, "a plurality of" means two or more, unless otherwise explicitly specified.
[0053] The above description is merely a specific embodiment of this disclosure, but the scope of protection of this disclosure is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this disclosure should be included within the scope of protection of this disclosure. Therefore, the scope of protection of this disclosure should be determined by the scope of the claims.
Claims
1. A self-generating acid system, characterized in that, include: The autogenous acid precursor comprises at least one ester compound that can generate an organic acid in a hydrolysis reaction; A nanocatalyst having a magnetic core, a mesoporous shell covering the magnetic core, and a catalytically active component loaded in the pores of the mesoporous shell; The nanocatalyst exhibits first catalytic activity for the hydrolysis of the authigenic acid precursor when the temperature is below a first temperature threshold, and second catalytic activity for the hydrolysis of the authigenic acid precursor when the temperature is above a second temperature threshold, wherein the first temperature threshold is lower than the second temperature threshold and the second catalytic activity is higher than the first catalytic activity.
2. The self-generating acid system according to claim 1, characterized in that, The catalytically active component includes transition metal oxides; the transition metal oxides are at least one of copper oxide, zinc oxide, and manganese dioxide.
3. The self-generating acid system according to claim 1 or 2, characterized in that, The magnetic core is nano-iron oxide particles, the mesoporous shell is a mesoporous silica shell, and the catalytically active component is copper oxide ultrafine nanoparticles loaded in the pores of the mesoporous silica shell.
4. The self-generating acid system according to claim 2, characterized in that, The concentration of the nanocatalyst in the authigenic acid system is 0.1% w / v to 1.0% w / v, and the weight of the authigenic acid precursor is 15-30 parts.
5. The self-generating acid system according to claim 1, characterized in that, The authigenic acid precursor is one or more of methyl formate, methyl acetate, and methyl lactate.
6. The self-generating acid system according to claim 1, wherein the acid-generating system further comprises a dispersant and a base liquid; the dispersant is sodium citrate or sodium dodecyl sulfate; and the base liquid is an aqueous solution of potassium chloride or an aqueous solution of ammonium chloride.
7. A method for preparing an autogenous acid system, characterized in that, The method includes: The authigenic acid precursor, nanocatalyst, and base liquid are mixed, and a dispersant is added. The mixture is stirred until the nanocatalyst is uniformly dispersed in the system to obtain the authigenic acid system. The authigenic acid precursor comprises at least one ester compound that can generate an organic acid in a hydrolysis reaction. The nanocatalyst has a magnetic core, a mesoporous shell covering the magnetic core, and a catalytically active component supported in the pores of the mesoporous shell. The nanocatalyst exhibits first catalytic activity for the hydrolysis reaction of the authigenic acid precursor when the temperature is below a first temperature threshold and second catalytic activity for the hydrolysis reaction of the authigenic acid precursor when the temperature is above a second temperature threshold, wherein the first temperature threshold is lower than the second temperature threshold and the second catalytic activity is higher than the first catalytic activity.
8. The preparation method according to claim 7, characterized in that, The nanocatalyst was prepared in advance by the following method: Magnetic nanoparticles were synthesized using a hydrothermal method to serve as the magnetic core. A mesoporous silica shell is coated onto the outside of the magnetic nanoparticles using an improved Stöber method. A catalytically active component, including a transition metal oxide, is loaded into the pores of the mesoporous silica shell by impregnation and calcination.
9. The application of the self-generating acid system according to any one of claims 1 to 6, characterized in that, include: The autogenous acid system is pumped into the wellbore, so that the autogenous acid system maintains first catalytic activity in the wellbore environment below the first temperature threshold, and the hydrolysis reaction of the autogenous acid precursor proceeds at a first rate. The authigenic acid system is continuously injected into a reservoir above a second temperature threshold, and the nanocatalyst is activated to a second catalytic activity, catalyzing the hydrolysis of the authigenic acid precursor at a second rate to generate organic acids, where the second rate is higher than the first rate. The generated organic acid is brought into contact with the reservoir rock to undergo an acid-rock reaction, thereby etching the reservoir.
10. The application according to claim 9, characterized in that, Also includes: After acidification, the nanocatalyst carried in the backflow solution is recovered and reused.